Hubungan Asupan Gizi (Lemak, Serat, Natrium), Stress Kerja dan Status Gizi dengan Kejadian Hipertensi pada Masyarakat - Angellia Rizqullah; Hidayatusy Syukrina Puteri; Dewi Woro Astuti (Jurnal Kebidanan dan Keperawatan Medika, 2026)
The World Health Organization (WHO) revealed the prevalence of hypertension worldwide in 2023, with an estimated 1.28 billion people aged 30–79 years, while in Indonesia, the prevalence was 30.18% for those aged >18 years in 2023. Nutritional status is one of the contributing factors to hypertension. Many individuals with hypertension are caused by poor nutritional status. One key aspect of achieving optimal health is ensuring good nutritional status. Adequate and balanced nutrient intake contributes to healthy nutritional status. This study aims to determine the relationship between nutritional intake (fat, fiber, sodium), work stress, and nutritional status with the incidence of hypertension in the community of Beringin Lubai Village, Muara Enim Regency, in 2025. This study used a cross-sectional research design with a sample size of 98 respondents. The sampling technique used random sampling. The results of the study were analyzed using Pearson's correlation test. The results showed that there was a relationship between nutrient intake and the incidence of hypertension (fat = 0.036, fiber = 0.025, sodium = 0.022), there was a relationship between work stress and the incidence of hypertension with a p-value of 0.015, and there was a relationship between nutritional status and the incidence of hypertension with a p-value of 0.030.